1978
DOI: 10.1152/jappl.1978.44.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and waking responses to hypoxia in sleeping dogs

Abstract: We examined waking and ventilatory responses to acute hypoxia in four dogs during natural sleep. Progressive hypoxia was induced by a rebreathing technique in which alveolar CO2 pressure (PACO2) was held at the eucapnic level. Arterial O2 saturation (SaO2) was measured with an ear oximeter, and sleep stage was determined by electroencephalographic and behavioral criteria. Arousal from eucapnic hypoxia occurred at a SaO2 of 87.5 +/- 2.6% (mean +/- SE) during slow-wave sleep (SWS), and at a SaO2 of 70.5 +/- 3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 0 publications
6
67
1
1
Order By: Relevance
“…Acute hypercapnia is a potent stimulus for arousal from sleep (19,20) and can also activate limbic structures, leading to the experience of dyspnea (21) and panic (22). Functional MRI studies have shown that hypercapnia and hypoxia induced by brief apnea cause an increase in activity within the thalamus and cerebral cortex (23).…”
mentioning
confidence: 99%
“…Acute hypercapnia is a potent stimulus for arousal from sleep (19,20) and can also activate limbic structures, leading to the experience of dyspnea (21) and panic (22). Functional MRI studies have shown that hypercapnia and hypoxia induced by brief apnea cause an increase in activity within the thalamus and cerebral cortex (23).…”
mentioning
confidence: 99%
“…As in most studies, the greatest depression in the ventilatory response to hypercapnia occurred during REM sleep (Phillipson et al 1977;Gothe et al 1981; Hedemark & Kronenberg 1982;Berthon-Jones & Sullivan, 1984). The mechanism of sleep-induced reduction of CO2 chemosensitivity is still not well understood.…”
Section: Discussionmentioning
confidence: 94%
“…Phillipson et al (1976Phillipson et al ( , 1977 introduced the chronic dog model to study the influence of sleep on respiration. Measurement of breathing pattern was performed in these studies using a chronic tracheostoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations